Soil bio-cementation treatment strategies: state-of-the-art review - Omoregie, Armstrong Ighodalo; Muda, Khalida; Ong, Dominic Ek Leong; Ojuri, Oluwapelumi Olumide; Bakri, Muhammad Khusairy Bin; Rahman, Md Rezaur; Basri, Hazlami Fikri; Ling, Yong Ee (Geotechnical research, 2024)
Bio-cementation is a new sustainable approach that has gained popularity due to its low energy and carbon dioxide footprint compared with those of existing technologies for geotechnical and geoenvironmental engineering applications. Bio-cementation is a soil improvement technique that involves binding the pore space of soil particles with calcium carbonate minerals by microbially induced carbonate precipitation (MICP) and filling the soil pore space. The purpose of this paper is to present the current state of the art and a comprehensive discussion on the development of bio-cementation for soil improvement/reinforcement. Premixing, injection, immersing and surface percolation are identified as four distinct bio-cementation treatment techniques. Furthermore, scholars have reported employing ureolytic bacteria such as Sporosarcina pasteurii, Bacillus sphaericus and Lysinibacillus sphaericus isolated from corals, limestone caves, soils, waste materials, seawater and other sources to accomplish effective bio-cementation. Some of the major issues (bacterial cultivation costs and ammonium production) that impede its industrial potential and promising remedial techniques are also discussed. This state-of-the-art review also discusses the benefits and drawbacks of bio-cementation compared with traditional approaches. The significance of enzyme-induced carbonate precipitation as a soil bio-cementation alternative to MICP is also highlighted. Finally, the sustainable procedure, bio-cementation principles and future implications are discussed.